THU0097 Impact of Patient Support Program use on Clinical Outcomes Among Patients with Rheumatoid Arthritis. (9th June 2015) - van den Bosch, F.; Wassenberg, S.; Ostor, A.; Varothai, N.; Garg, V.; Kalabic, J.
Abstract : Background: Patients (pts) may benefit from the use of a patient support program (PSP) to manage their rheumatoid arthritis (RA). Objectives: To assess the impact of PSP utilization on adalimumab (ADA) effectiveness for RA treatment in clinical settings. Methods: PASSION (NCT01383421 ) is a post-marketing observational study to explore and describe the effectiveness of ADA on the course of RA treatment and pt satisfaction over time in the context of utilization of the PSP. The study enrolled pts with moderate to severe RA with an insufficient response to ≥1 disease-modifying antirheumatic drug (DMARD) and initiated ADA at participating sites in the EU, Mexico, Puerto Rico, and Australia. Pts had to be ADA-naive and treated with ≤1 prior biologic DMARD. Pts were prescribed ADA according to the local product label and had an option to utilize the PSP while participating in the study. The PSP comprised "Core elements" (starter pack, call center/hotline, nursing services, educational material, and injection guide; offered in all participating countries) and "Other elements" (eg, refill reminders, email, newsletters, support groups, home delivery, and financial assistance; varied by country). The primary endpoint is the % of pts achieving the minimal clinically important difference (MCID; improvement of ≥0.22) in the Health Assessment Questionnaire Disability Index (HAQ-DI) at week (wk) 78 vs baseline (BL). Secondary clinical parameters include % of pts achieving MCID in HAQ-DI at wks 12, 24, 36, 52, and 64 vs BL and changes in the 28-joint Disease Activity Score (DAS28), Simplified Disease Activity Index (SDAI), and Clinical Disease Activity Index (CDAI). Results: Most enrolled pts in this interim analysis (n=852) completed 52 wks of treatment. The mean age at BL was 54.1 y; 76.1% of pts were female, and the mean duration of RA was 7.8 y. Mean BL disease scores were 1.5 for HAQ-DI, 5.3 for DAS28 based on C-reactive protein (CRP), 35.8 for SDAI, and 33.4 for CDAI. Prior biologic DMARD exposure was 17.4%. Overall, 49.9% of enrolled pts utilized the PSP. Improvement in physical functioning was greater at all study time points in pts utilizing the PSP vs those who were non-PSP users, as reflected by mean decreases of 0.61 and 0.46, respectively, in HAQ-DI from BL to wk 52 ( P =0.07). More pts using the PSP achieved an MCID in the HAQ-DI vs non-PSP users (73.8% vs 67.2%) at wk 52 ( P =0.18). Significant changes ( P ≤0.005) from BL to wk 52 were observed for pts using the PSP vs non-PSP users in DAS28(CRP) (−2.88 vs −2.13), SDAI (−30.57 vs −21.65), and CDAI (−26.98 vs −20.75) scores. Study discontinuation rates were significantly ( P =0.003) lower among PSP users vs non-PSP users (20.0% vs 29.0%). Conclusions: Interim data showed that, in pts with moderate to severe RA who initiated ADA, better improvement in functional and clinical outcomes was achieved in the PSP users vs the non-PSP users. Improvements were maintained at all time points and continued to increase throughout the study, most likely due to better adherence rates among PSP users. Acknowledgements: AbbVie funded the study and the analysis, and approved the abstract for submission. Medical writing assistance was provided by Katherine Groschwitz and Michael Theisen of Complete Publication Solutions, LLC, and was supported by AbbVie. Disclosure of Interest: F. Van den Bosch Consultant for: received speaker and/or consultancy fees from AbbVie, Celgene, Janssen, Novartis, Pfizer, and UCB, S. Wassenberg Grant/research support from: participated in phase 3 and phase 4 studies sponsored by AbbVie, Speakers bureau: received speakers honoraria of less than 5.000 € in the last 2 years from AbbVie; also received support, including speaker and/or consultancy fees and attendance at conferences, from Chugai, Janssen, MSD, Novartis, Pfizer, Roche, and UCB, A. Ostor Grant/research support from: received support from (including attendance at conferences), undertakes clinical trials and acts as a consultant to Roche, Chugai, MSD, AbbVie, Pfizer, Novartis, Napp, and BMS, N. Varothai Shareholder of: AbbVie, Employee of: AbbVie, V. Garg Shareholder of: AbbVie, Employee of: AbbVie, J. Kalabic Shareholder of: AbbVie, Employee of: AbbVie